2007
DOI: 10.1080/10407780601112803
|View full text |Cite
|
Sign up to set email alerts
|

Modeling IC Engine Conjugate Heat Transfer Using the KIVA Code

Abstract: Locating hotspots in metal engine components can be used as an impetus to design a better cooling system. This study focuses on a numerical investigation of a three-dimensional (3-D) transient heat transfer process for a Ford 5.4-L V8 engine. A 3-D transient finitevolume method to solve the heat conduction equation is presented first. This is followed by the implementation of the coupling equations at the gas-solid interface into the KIVA code. The numerical model is validated by a one-dimensional heat conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Despite the inherent differences in the orders of magnitude in time scales associated with heat transfer in the fluids and the solids, these studies are carried out with in-cylinder gases and engine solid walls. Egel Urip [9] documented the coupled approach of evaluating heat transfer between combustion gases and solids within the same code. It was concluded that the best way to transfer combustion load between in-cylinder gases and solids is by using the convective conditions, i.e., heat transfer coefficients (HTC) coupled with near wall gas temperatures (Tgas) rather than the heat flux itself.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the inherent differences in the orders of magnitude in time scales associated with heat transfer in the fluids and the solids, these studies are carried out with in-cylinder gases and engine solid walls. Egel Urip [9] documented the coupled approach of evaluating heat transfer between combustion gases and solids within the same code. It was concluded that the best way to transfer combustion load between in-cylinder gases and solids is by using the convective conditions, i.e., heat transfer coefficients (HTC) coupled with near wall gas temperatures (Tgas) rather than the heat flux itself.…”
Section: Introductionmentioning
confidence: 99%
“…CHT can be used to model the coupled heat transfer between the engine solid components and liquid cooling jacket, while the in-cylinder flow is simulated separately using CFD [27,29,30,32]. Some studies only considered the coupling of the in-cylinder gas and solid components [34,35]. Or, CHT can be used to simulate the heat transfer between the engine solid components and the in-cylinder flow, while the liquid cooling jacket is simulated using CFD [28,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that the predicted heat flux from CHT can differ more than 20% from the heat flux obtained from uniform wall temperature boundary condition. Urip et al [34] implemented the CHT model in KIVA-3V, but excluded the CHT calculation in the valves, and only simulated the engine cycle from Intake Valve Closing (IVC) to Exhaust Valve Opening (EVO). Significant heat transfer can occur during valve events, and the entire engine cycle should be simulated.…”
Section: Introductionmentioning
confidence: 99%
“…Predicting the temperature field accurately is the premise in designing a high-performance cooling system. With the rapid development of CFD technology and computer science, three-dimensional numerical simulations using the conjugate heat transfer (CHT) algorithm have become effective methods for accurately predicting the temperature field of turbine blades and other hot-end components [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%